Molecular mechanism of preQ1 riboswitch action: a molecular dynamics study - Banáš, Pavel; Sklenovský, Petr; Wedekind, Joseph E; Šponer, Jiří; Otyepka, Michal (The journal of physical chemistry. B, 2012)
Riboswitches often occur in the 5'-untranslated regions of bacterial mRNA where they regulate gene expression. The preQ(1) riboswitch controls the biosynthesis of a hypermodified nucleoside queuosine in response to binding the queuosine metabolic intermediate. Structures of the ligand-bound and ligand-free states of the preQ(1) riboswitch from Thermoanaerobacter tengcongensis were determined recently by X-ray crystallography. We used multiple, microsecond-long molecular dynamics simulations (29 μs in total) to characterize the structural dynamics of preQ(1) riboswitches in both states. We observed different stabilities of the stem in the bound and free states, resulting in different accessibilities of the ribosome-binding site. These differences are related to different stacking interactions between nucleotides of the stem and the associated loop, which itself adopts different conformations in the bound and free states. We suggest that the loop not only serves to bind preQ(1) but also transmits information about ligand binding from the ligand-binding pocket to the stem, which has implications for mRNA accessibility to the ribosome. We explain functional results obscured by a high salt crystallization medium and help to refine regions of disordered electron density, which demonstrates the predictive power of our approach. Besides investigating the functional dynamics of the riboswitch, we have also utilized this unique small folded RNA system for analysis of performance of the RNA force field on the μs time scale. The latest AMBER parmbsc0χ(OL3) RNA force field is capable of providing stable trajectories of the folded molecule on the μs time scale. On the other hand, force fields that are not properly balanced lead to significant structural perturbations on the sub-μs time scale, which could easily lead to inappropriate interpretation of the simulation data.
Keywords: Crystallography, X-Ray; Thermoanaerobacter; RNA, Bacterial; bakteriální RNA; Riboswitch; riboswitch; simulace molekulární dynamiky; molekulární modely; Molecular Dynamics Simulation; Models, Molecular; krystalografie rentgenová